Da receita à paixão: a mise en abyme em Clarice Lispector - Alonso, Mariângela [UNESP] (2015)
Clarice Lispector's narratives expand beyond the fictional spaces, characterized by refusal to closed and finished narrative to seek liquid and unfinished forms, which perpetually fall apart to be built again in a circular motion, then the author weaving and unweaving the text in a continuous entanglement. Thus, the textual mass en abyme indicates the intersection of several major chains, i.e., a narrative mirror game in which each work ending tends to close a cycle, resuming the next operation and so on, as the eternal Russian dolls or flagship Chinese boxes. In this sense, this research proposes the study of modern writing of Clarice Lispector process, using as corpus the narratives Meio cômico, mas eficaz; Receita de assassinato (de baratas); A quinta história and A paixão segundo G.H. The scope of work is to examine the relationships between the above texts, according to studies of intertextuality. The process indicated before is defined as the resumption of a text on the other and thus the relationships between different texts by different authors. However, this research focuses on texts by the same author, basing on what the theoretical Gérard Genette conceived as autotextuality or intratextuality, a phenomenon characterized by reference to the work itself. Therefore, we seek to undertake a possible way of analysis of the mentioned texts, guiding us by Lucien Dällenbach (1977) studies, Gérard Genette (1982), Jean Ricardou (1978), among others